2020
DOI: 10.1128/msphere.00097-20
|View full text |Cite
|
Sign up to set email alerts
|

The Diversity Outbred Mouse Population Is an Improved Animal Model of Vaccination against Tuberculosis That Reflects Heterogeneity of Protection

Abstract: Many studies of Mycobacterium tuberculosis infection and immunity have used mouse models. However, outcomes of vaccination and challenge with M. tuberculosis in inbred mouse strains do not reflect the full range of outcomes seen in people. Previous studies indicated that the novel Diversity Outbred (DO) mouse population exhibited a spectrum of outcomes after primary aerosol infection with M. tuberculosis. Here, we demonstrate the value of this novel mouse population for studies of vaccination against M. tuberc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
54
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(66 citation statements)
references
References 53 publications
4
54
0
Order By: Relevance
“…We showed that supersusceptible DO mice develop pulmonary TB with large necrotizing granulomas and abundant M.tb bacilli, while those that survive longer develop non-necrotic lymphocyte-rich granulomas. Published elsewhere, we confirmed that DO mice are not immune deficient or highly susceptible to other mycobacteria, and they generate antigenspecific immunity against M.tb [16,23,24]. Together, these results support our conclusion that DO mice are a valuable animal model of TB.…”
Section: Discussionsupporting
confidence: 90%
“…We showed that supersusceptible DO mice develop pulmonary TB with large necrotizing granulomas and abundant M.tb bacilli, while those that survive longer develop non-necrotic lymphocyte-rich granulomas. Published elsewhere, we confirmed that DO mice are not immune deficient or highly susceptible to other mycobacteria, and they generate antigenspecific immunity against M.tb [16,23,24]. Together, these results support our conclusion that DO mice are a valuable animal model of TB.…”
Section: Discussionsupporting
confidence: 90%
“…In a longitudinal study, J:DO mice were found to be more susceptible to Mycobacterium tuberculosis, as they exhibited increased lung bacterial load and pathology and died 80 days post-infection, whereas B6 mice survived until 113 days. 47 Although no sex-based differences were observed in innate responses, S. aureusinfected J:DO mouse eyes had slightly elevated levels of IL-1β and CXCL2/MIP2 as compared to C57BL/6 mice, whereas TNF-α and IL-6 levels were similar. In systemic bacterial infections, diversity outbred mice have been shown to evoke a strong chemokine response.…”
Section: Discussionmentioning
confidence: 85%
“…The J:DO founders were derived from eight inbred strains, including traditional laboratory strains such as C57BL/6 and A/J, as well as three wild-derived mice strains (CAST/EiJ, PWK/PhJ, and WSB/EiJ) through collaborative cross. [45][46][47] As these mice have been used to account for genetic diversity in bacterial and viral infections, 46,47 S. aureus endophthalmitis was induced in both male and female J:DO mice (6-8 weeks old). Our time-course study revealed that, like C57BL/6 mice, J:DO mice developed severe endophthalmitis resulting in a time-dependent increase in corneal haze, anterior chamber opacity, and hypopyon (Fig.…”
Section: Genetic Diversity Is a Dispensable Biological Variable In Bamentioning
confidence: 99%
“…One third of DO mice are supersusceptible (SS) to Mtb, developing early-onset disease within 8 weeks of aerosol infection by ~25 bacilli, significantly reducing survival compared to age-and sex-matched non-infected DO mice or to Mtb-infected C57BL/6J inbred mice ( Figure 1A). The SS phenotype is consistent across sexes, institutions, and aerosol infection methods 11,25 .…”
Section: Mtb Infection and Pulmonary Tb In Do Micementioning
confidence: 79%
“…Disease onset in SS DO mice began as early as 4 days afterMtb infection and peaked at 18 days post-infection (C).Immune deficiency does not explain early-onset TB in the DO population. DO mice generate Mtb antigen specific TH1 immunity, respond to M. bovis BCG vaccination without developing BCGosis11,16,25 and generate TH2 and TH17 immune mediators (Supplemental Figures). Our prior work identified three neutrophil chemokines (CXCL1, CXCL2, CXCL5) that diagnosed SS DO mice with modest accuracy11 .…”
mentioning
confidence: 99%